Seyyed Hossein Nasr's Concept of The Relationship Between Man, Nature, and God - Salamuddin Salamuddin (Institut Agama Islam Negeri Madura, 2017)
The most complex problem in the world nowadays is subjugating human’s egocentrism as a superior human being toward the nature, and exploiting the nature on the strength of human needs and interests created the new problem for the human itself. The nature starts to turn against us using its own way, and this problem slowly threatens the continuity of life chain for all beings in this earth. Owing to this problem, a contemporary philosopher, Sayyed Hosen Nasr expressed his thought to criticize the modern civilization with the globalization that continuously devastates the nature without considering how life goes well and how to make this not harm each other. One of the thoughts created by Nasr is his idea about ‘nature’, how to revive the nature, and the idea of eco-theology in this paper is the introduction of a piece of his thoughts that truly criticizes the modernity conception that revives the nature slowly. The result proposed by Nasr shows that he wants to reconcile the modernity without ‘God’ soul and turns it into the religious modernity that shows the nature is not supposed to be treated as the human wants, but the nature must be treated like the equal beings, to be maintained and to be preserved, because the human life is determined by how the nature goes.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1203